2017
DOI: 10.1155/2017/2592496
|View full text |Cite
|
Sign up to set email alerts
|

The Proangiogenic Capabilities of Malignant Ascites Generated by Aggressive Ovarian Tumors

Abstract: Here we examined whether malignant ascites may determine ovarian tumor angiogenesis, and if so whether ascites generated by highly aggressive serous and undifferentiated cancers are more proangiogenic than those from less aggressive clear cell and endometrioid tumors. Angiogenesis was analyzed according to expression of CD31, CD34, and connexin 43. Proliferation and migration of endothelial cells were tested using fluorescence-based methods. The quantification of angiogenic agents and hypoxia-inducible factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Recent data indicated that a large amount of ascites at the initial diagnosis of EOC was associated with worse prognosis, which may be related in part to decreased possibility of performing complete tumor resection as well ( 17 ). Additionally, ascites volume strongly promotes angiogenesis and increases cancer cells’ transmesothelial invasion ( 18 , 19 ), and a more interesting finding was that the expression of multidrug resistance associated protein in ovarian cancer cells was caused by increased ascites volume ( 20 ), but exact mechanism is yet unclear. Our results demonstrate the median of ascites volume in STS was 700 mL compared to that of LTS, which was 300 mL, but there is no significant difference, and we need to include more patients to explore the impact of ascitic fluid volume on survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicated that a large amount of ascites at the initial diagnosis of EOC was associated with worse prognosis, which may be related in part to decreased possibility of performing complete tumor resection as well ( 17 ). Additionally, ascites volume strongly promotes angiogenesis and increases cancer cells’ transmesothelial invasion ( 18 , 19 ), and a more interesting finding was that the expression of multidrug resistance associated protein in ovarian cancer cells was caused by increased ascites volume ( 20 ), but exact mechanism is yet unclear. Our results demonstrate the median of ascites volume in STS was 700 mL compared to that of LTS, which was 300 mL, but there is no significant difference, and we need to include more patients to explore the impact of ascitic fluid volume on survival.…”
Section: Discussionmentioning
confidence: 99%
“…This term refers to pathologic fluid that accumulates in the abdomen in a group of patients, mostly in the advanced stages of the disease [2]. Malignant ascites have been found to create hospitable conditions for tumor expansion by suppressing peritoneal inflammatory reactions [3], inducing angiogenesis [4], and promoting cancer cell proliferation [5] and migration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evidence supports the critical role of VEGF in ascites formation and ovarian cancer progression and recurrence. Components of ascites are known to have potent angiogenic capabilities, and such components promote hypervascularization of aggressive tumors 31 . Some studies had shown that the combination of anti‐angiogenic agents such as bevacizumab with standard chemotherapy would improve PFS and OS for the patients with ascites 32 .…”
Section: Discussionmentioning
confidence: 99%